2022
DOI: 10.47750/pnr.2022.13.s06.345
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Micro Esthetics in Patients Reporting for Orthodontic Treatment

Abstract: Background: Patients today seeking esthetic treatment are looking for enhancement of their appearance for improved quality of life. We advocate the use of the term “appearance” in conjunction with the term “esthetics'' because it involves a broader assessment of the patient other than the smile. So, in orthodontic diagnosis and treatment planning we have created an approach in evaluation divided into three divisions:1 Macro Esthetics—this includes the profile, vertical facial dimensions—in other words—the face… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Five studies[ 8 9 10 11 12 ] were considered to be relevant to the objectives of our study and as such were included in the review and subsequent meta-analysis. The NOS evaluation of the included studies reveals varying levels of risk of bias in different domains as shown in Figure 2 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Five studies[ 8 9 10 11 12 ] were considered to be relevant to the objectives of our study and as such were included in the review and subsequent meta-analysis. The NOS evaluation of the included studies reveals varying levels of risk of bias in different domains as shown in Figure 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The study by Sunar et al . [ 11 ] has high study design quality, but the representativeness of the exposed cohort, selection of the nonexposed cohort, ascertainment of exposure, comparability of cohorts based on the design or analysis, and assessment of outcome are all unclear. Finally, the study by Tauheed et al .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations